UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA DI KALANGAN PELAJAR - Vidi Galenso (The Juris, 2022)
Narcotics are substances or drugs derived from plants or non-plants, both synthetic and semi-synthetic, which can cause a decrease or change in consciousness, loss of taste, reduce to eliminate pain, and can cause dependence. Narcotics abuse can be categorized as a crime as regulated in Law Number 35 of 2009 concerning Narcotics. The research method used is a normative juridical research method. Sources of legal materials used include primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials uses library research. And the technique of analyzing legal materials uses descriptive qualitative techniques. The results of the study show that in Indonesia, drug addicts are growing rapidly. The drug addicts are generally between the ages of 11 to 24 years. This means that this age is productive age or student age. The impact of drug abuse can damage the nervous system, so that you cannot think clearly, easily forget, have difficulty concentrating. Therefore, efforts to prevent and control drugs are needed, especially among teenagers/students. Overcoming drug abuse is not only the responsibility of the government alone, but these efforts are also the responsibility of the general public starting from the smallest group, namely the family environment, school environment, and community environment where teenagers actualize themselves.